Silicon-based negative electrode, preparation method thereof and battery
By constructing a buffer layer of covalent organic framework material on the surface of the silicon nanosheets of the silicon-based anode, the problem of high expansion rate of the silicon-based anode is solved, and the cycle stability and electrochemical performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411630949.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-11
AI Technical Summary
The high expansion rate of the silicon-based negative electrode leads to particle powdering, electrode structure failure and SEI repeated growth, affecting the electrochemical performance of the battery.
By mixing and heat-treating the covalent organic framework material precursor with the silicon nanosheet, a buffer layer of covalent organic framework material is generated and adhered to the surface of the silicon nanosheet, thereby reducing the expansion rate of the silicon-based negative electrode.
Effectively suppress and buffer the huge volume changes caused by silicon nanosheets during charging and discharging, reduce the expansion rate of the silicon-based negative electrode, and improve the cycle stability and electrochemical performance of the battery.
Smart Images

Figure CN119601601A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of silicon-based negative electrodes, and in particular to a silicon-based negative electrode and a preparation method and a battery thereof. Background Art
[0002] With the rapid development of the new energy industry, the range anxiety and safety anxiety of electric vehicles are becoming more and more prominent. Solid-state batteries have become an important way to solve the two major anxieties of new energy vehicles due to their high energy density and high safety. In order to significantly increase the energy density of solid-state batteries, the positive and negative electrodes often use high-gram capacity material systems, usually using a silicon-based negative electrode mixed with graphite and silicon materials and a high-nickel ternary to form a solid-state battery.
[0003] Although the silicon-based negative electrode has a high specific capacity, its high expansion rate will lead to problems such as particle pulverization, electrode structure destruction, and repeated growth of SEI, which will affect the electrochemical properties of the battery. Summary of the invention
[0004] The present application provides a silicon-based negative electrode and a preparation method and a battery thereof to solve the following technical problem: how to reduce the expansion rate of the silicon-based negative electrode.
[0005] In a first aspect, the present application provides a method for preparing a silicon-based negative electrode, the method comprising:
[0006] Obtaining a covalent organic framework material precursor;
[0007] The covalent organic framework material precursor is first mixed with silicon nanosheets to obtain a mixed solution;
[0008] The mixed solution is heat-treated to make the covalent organic framework material precursor undergo a polymerization reaction to generate a covalent organic framework material buffer layer, and the covalent organic framework material buffer layer is attached to at least a portion of the surface of the silicon nanosheet to obtain a silicon-based negative electrode.
[0009] Optionally, the step of obtaining a covalent organic framework material precursor comprises:
[0010] The tri(4-aminophenyl)amine, the dibasic anhydride monomer and the solvent are mixed for a second time to obtain a covalent organic framework material precursor.
[0011] Optionally, the dibasic anhydride monomer includes at least one of the following: pyromellitic dianhydride, naphthalenetetracarboxylic dianhydride, and perylenetetracarboxylic dianhydride.
[0012] Optionally, the molar ratio of the tris(4-aminophenyl)amine to the dibasic anhydride monomer is (3:2) to (4:2).
[0013] Optionally, the solvent is an amide solvent.
[0014] Optionally, the solvent is 150 mL to 250 mL relative to 1 mol of the dibasic anhydride monomer.
[0015] Optionally, the molar ratio of the silicon nanosheets to the dibasic anhydride monomer is (20:1) to (40:1).
[0016] Optionally, the process parameters of the heat treatment include: a heating temperature of 120° C. to 180° C. and a heating time of 56 h to 80 h.
[0017] In a second aspect, the present application provides a silicon-based negative electrode prepared by the method described in any one of the first aspects.
[0018] In a third aspect, the present application provides a battery, comprising the silicon-based negative electrode as described in any one of the second aspects.
[0019] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0020] The preparation method of the silicon-based negative electrode provided in the embodiment of the present application includes: obtaining a covalent organic framework material precursor; first mixing the covalent organic framework material precursor with a silicon nanosheet to obtain a mixed solution; heat treating the mixed solution to make the covalent organic framework material precursor undergo a polymerization reaction to generate a covalent organic framework material buffer layer, and make the covalent organic framework material buffer layer adhere to at least part of the surface of the silicon nanosheet to obtain a silicon-based negative electrode. The covalent organic framework material has high chemical stability and large elasticity. The polymer chain will not break after being subjected to a certain pressure, and will return to its original state after the pressure is removed; the covalent organic framework material precursor and the silicon nanosheet are compounded by heat treatment to obtain a silicon-based negative electrode with a covalent organic framework material buffer layer on the surface, which means that the surface of the silicon nanosheet has a covalent organic framework material buffer layer. When the silicon nanosheet expands, the covalent organic framework will expand slightly together, but it will not be as large as the expansion rate of the silicon nanosheet itself, thereby playing a certain binding role on the silicon nanosheet. When the silicon nanosheet shrinks, the covalent organic framework also shrinks and recovers to its original state. Therefore, its strong constraint buffering effect can fully suppress and buffer the huge volume changes caused by silicon nanosheets during the charging and discharging process, that is, reduce the expansion rate of the silicon-based negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0023] Figure 1 A schematic diagram of a process for preparing a silicon-based negative electrode provided in an embodiment of the present application;
[0024] Figure 2 A schematic diagram of a reaction formula for preparing a silicon-based negative electrode provided in an embodiment of the present application. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0026] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0027] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "include", "comprise", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, wherein a, b, c can be single or multiple, respectively. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the molar ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond one to one with the proportional numbers in the proportional formula in the order of description, that is, the mole of substance A: the mole of substance B: the mole of substance C = 1:2:3.
[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0029] In a first aspect, the present application provides a method for preparing a silicon-based negative electrode. Figure 1 For a schematic diagram of a method for preparing a silicon-based negative electrode provided in an embodiment of the present application, see Figure 1 , the method comprising:
[0030] S1, obtaining a covalent organic framework material precursor;
[0031] In some embodiments, the step of obtaining a covalent organic framework material precursor comprises:
[0032] The tri(4-aminophenyl)amine, the dibasic anhydride monomer and the solvent are mixed for a second time to obtain a covalent organic framework material precursor.
[0033] In the embodiment of the present application, tri(4-aminophenyl)amine (TAPA) has a stable molecular structure, a dibasic anhydride monomer is used as a conjugated anhydride, a solvent dissolves tri(4-aminophenyl)amine and the dibasic anhydride monomer, and tri(4-aminophenyl)amine and the dibasic anhydride monomer are polymerized to obtain a covalent organic skeleton material with a stable structure. Covalent organic skeleton material is an emerging crystalline porous polymer material composed of organic molecules and connected by covalent bonds. The covalent organic skeleton material has the characteristics of high chemical stability and thermal stability, structural diversity and designability, and a regular pore structure, and therefore plays a certain positive role in the subsequent suppression and buffering of the huge volume changes caused by silicon nanosheets during the charge and discharge process. The covalent organic skeleton obtained by the polymerization of the covalent organic skeleton material precursor does not contain any metal elements, and the synthetic raw materials used are all common organic raw materials, which are widely available, pollution-free, and low in cost.
[0034] In some embodiments, the dibasic anhydride monomer includes at least one of the following: pyromellitic dianhydride, naphthalenetetracarboxylic dianhydride, and perylenetetracarboxylic dianhydride.
[0035] In the embodiments of the present application, pyromellitic anhydride, naphthalenetetracarboxylic anhydride, and perylenetetracarboxylic anhydride are all conjugated anhydrides, and the conjugated dianhydride monomer can be a combination of one or more of pyromellitic anhydride, naphthalenetetracarboxylic anhydride, and perylenetetracarboxylic anhydride, thereby polymerizing with tri(4-aminophenyl)amine to form a covalent organic skeleton material with a stable structure.
[0036] In some embodiments, the molar ratio of the tris(4-aminophenyl)amine to the dibasic anhydride monomer is (3:2) to (4:2).
[0037] In the embodiment of the present application, the molar ratio of tris(4-aminophenyl)amine to dibasic anhydride monomer can be (3:2) to (4:2), so as to achieve polymerization of tris(4-aminophenyl)amine and dibasic anhydride monomer to form a stable covalent organic skeleton material. Exemplarily, the molar ratio of the above tris(4-aminophenyl)amine to dibasic anhydride monomer can be 3:2, 4:2, 4:3, etc., and further, the molar ratio of the above tris(4-aminophenyl)amine to dibasic anhydride monomer can be 3:2.
[0038] In some embodiments, the solvent is an amide solvent.
[0039] In the embodiment of the present application, the solvent may be an amide solvent, which has good solubility and thermal stability, so that tris(4-aminophenyl)amine and dibasic anhydride monomers can be fully dissolved. Exemplarily, the amide solvent may be a combination of one or more of N-N'-dimethylacetamide (DMF) and N-N'-dimethylformamide.
[0040] In some embodiments, the solvent is 150 mL to 250 mL relative to 1 mol of the dibasic anhydride monomer.
[0041] In the embodiment of the present application, the solvent can be 150mL to 250mL relative to 1mol of dianhydride monomer, so as to keep tri(4-aminophenyl)amine and dianhydride monomer within a suitable concentration range, thereby ensuring that the subsequent polymerization obtains an ideal covalent organic framework material. If the amount of solvent used is too much and exceeds 250mL, to a certain extent, the concentration of tri(4-aminophenyl)amine and dianhydride monomer will be low, resulting in the defects of extended polymerization reaction time and incomplete reaction; if the amount of solvent used is too little and less than 150mL, to a certain extent, the concentration of tri(4-aminophenyl)amine and dianhydride monomer will be high, resulting in a too fast polymerization reaction speed, and ultimately it is difficult to form a uniform covalent organic framework material buffer layer on the surface of the silicon nanosheet. Exemplarily, relative to 1mol of dianhydride monomer, the solvent can be 150mL, 160mL, 170mL, 180mL, 190mL, 200mL, 210mL, 220mL, 230mL, 240mL, 250mL, etc.
[0042] S2, first mixing the covalent organic framework material precursor and the silicon nanosheets to obtain a mixed solution;
[0043] In some embodiments, the molar ratio of the silicon nanosheets to the dibasic anhydride monomer is (20:1) to (40:1).
[0044] In the embodiment of the present application, the above-mentioned covalent organic framework material can suppress and buffer the huge volume change caused by silicon nanosheets during the charge and discharge process. The molar ratio of silicon nanosheets to dibasic anhydride monomers can be (20:1) to (40:1), so as to maintain the balance between the silicon content and the covalent organic framework material content in the silicon-based negative electrode, so as to fully suppress and buffer the huge volume change caused by silicon nanosheets during the charge and discharge process. If the molar ratio of silicon nanosheets to dibasic anhydride monomers is higher than 40:1, to a certain extent, the generation amount of covalent organic framework materials will be low, and it will be difficult to exert the inhibitory expansion effect of covalent organic framework materials on silicon nanosheets; if the molar ratio of silicon nanosheets to dibasic anhydride monomers is lower than 20:1, to a certain extent, the silicon content in the silicon-based negative electrode will be low, thereby causing the reversible capacity of the silicon-based negative electrode to be greatly reduced. Exemplarily, the molar ratio of the above-mentioned silicon nanosheets to dibasic anhydride monomers can be 20:1, 25:1, 30:1, 35:1, 40:1, etc. In addition, the molar value of the silicon nanosheets is generally calculated based on the silicon in the silicon nanosheets. In the embodiments of the present application, pure silicon nanosheets are used, and the size of the silicon nanosheets may be 100 nm to 500 nm.
[0045] S3, heat-treating the mixed solution to make the covalent organic framework material precursor undergo a polymerization reaction to generate a covalent organic framework material buffer layer, and making the covalent organic framework material buffer layer adhere to at least a portion of the surface of the silicon nanosheet to obtain a silicon-based negative electrode.
[0046] In the embodiment of the present application, the covalent organic framework material has high chemical stability and large elasticity. The polymer chain will not break after being subjected to a certain pressure, and will return to its original state after the pressure is removed; the cost of silicon nanosheets is very low, the reversible capacity is very high, but the expansion rate is also very high, so the covalent organic framework is used to solve the high expansion rate problem of silicon nanosheets, thereby improving the industrial application of silicon nanosheets. By constructing the covalent organic framework material in situ on the surface of the silicon nanosheet, the silicon nanoparticles are bound in the organic framework, which is specifically embodied in that the covalent organic framework material precursor and the silicon nanosheet are compounded by heat treatment to obtain a sandwich silicon-based negative electrode with a covalent organic framework material buffer layer on the surface, which means that the surface of the silicon nanosheet has a covalent organic framework material buffer layer. When the silicon nanosheet expands, the covalent organic framework will expand slightly together, but it will not be as large as the expansion rate of the silicon nanosheet itself, thereby playing a certain binding role on the silicon nanosheet, and when the silicon nanosheet shrinks, the covalent organic framework also shrinks and recovers to its original state. Therefore, its strong restraint buffering effect can fully suppress and buffer the huge volume change caused by the silicon nanosheets during the charge and discharge process, that is, reduce the expansion rate of the silicon-based negative electrode. Figure 2 A schematic diagram of a silicon-based negative electrode preparation reaction provided in an embodiment of the present application; see Figure 2 , pyromellitic anhydride, TAPA and silicon nanosheets are subjected to a heating polymerization reaction to obtain a silicon-based negative electrode in which a covalent organic framework material buffer layer is uniformly attached to the silicon nanosheets.
[0047] In some embodiments, the process parameters of the heat treatment include: a heating temperature of 120° C. to 180° C. and a heating time of 56 h to 80 h.
[0048] In an embodiment of the present application, tri(4-aminophenyl)amine and dibasic anhydride monomers are polymerized by heat treatment to form a sandwich silicon-based negative electrode constrained by a covalent organic framework material. In the process parameters of the heat treatment, the heating temperature can be 120°C to 180°C, and the heating time can be 56h to 80h, so that tri(4-aminophenyl)amine and dibasic anhydride monomers can be fully polymerized, and a moderate polymerization reaction rate is maintained to obtain an ideal covalent organic framework material, and a uniform covalent organic framework material buffer layer is formed on the surface of the silicon nanosheet. If the heating temperature is too high or the heating time is too long, it will cause the polymerization reaction rate to be too fast to a certain extent, and it will be difficult to form a uniform covalent organic framework material buffer layer on the surface of the silicon nanosheet; if the heating temperature is too low or the heating time is too short, it is difficult to make tri(4-aminophenyl)amine and dibasic anhydride monomers polymerize. Exemplarily, the heating temperature may be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc., and the heating time may be 56h, 60h, 65h, 70h, 75h, 80h, etc.
[0049] In a second aspect, the present application provides a silicon-based negative electrode prepared by the method described in any one of the first aspects.
[0050] In the embodiments of the present application, a silicon-based negative electrode is prepared using the above method, wherein the strong constraint buffering effect of the covalent organic framework material can fully suppress and buffer the huge volume change caused by the silicon nanosheets during the charging and discharging process, that is, the expansion rate of the silicon-based negative electrode is greatly reduced, thereby maintaining the silicon nanosheets during the cycle process. The stress caused by excessive expansion will not cause pulverization, structural damage, etc., thereby improving its cycle stability.
[0051] The silicon-based negative electrode is realized based on the preparation method of the silicon-based negative electrode. The specific steps of the preparation method of the silicon-based negative electrode can refer to the above-mentioned embodiment. Since the silicon-based negative electrode adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.
[0052] In a third aspect, the present application provides a battery, comprising the silicon-based negative electrode as described in any one of the second aspects.
[0053] In the embodiment of the present application, the strong constraint buffering effect of the covalent organic framework material in the above-mentioned silicon-based negative electrode can fully suppress and buffer the huge volume change caused by the silicon nanosheet during the charge and discharge process, that is, greatly reduce the expansion rate of the silicon-based negative electrode, so as to keep the silicon nanosheet from being pulverized and structurally damaged due to the stress generated by excessive expansion during the cycle, thereby improving its cycle stability. The silicon-based negative electrode is applied to the battery to reduce the consumption of the electrolyte and promote the formation of a uniform, stable and firm SEI film (solid electrolyte layer), thereby improving the long cycle and rate performance of the battery cell. In addition, the covalent organic framework material buffer layer on the surface of the silicon nanosheet also plays an auxiliary bonding role. The organic groups rich in the skeleton make it easier to combine with the binder, and the covalent organic framework material buffer layer also has lithium storage performance, which will not significantly reduce the battery capacity, and is particularly suitable for lithium-ion batteries.
[0054] The battery is realized based on the above-mentioned silicon-based negative electrode. The specific preparation method of the silicon-based negative electrode can refer to the above-mentioned embodiment. Since the battery adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0055] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0056] Example 1
[0057] S11, obtaining a covalent organic framework material precursor;
[0058] Specifically, TAPA and pyromellitic anhydride were dissolved in DMF, the molar ratio of TAPA to pyromellitic anhydride was 3:2, and 200 mL of DMF was added for each mole of pyromellitic anhydride dissolved;
[0059] S21, first mixing the covalent organic framework material precursor and the silicon nanosheets to obtain a mixed solution;
[0060] Specifically, 200 nm average size silicon nanosheets are uniformly dispersed in the above covalent organic framework material precursor, the molar ratio of silicon nanosheets to pyromellitic anhydride is 20:1, and ultrasonic dispersion is adopted: power 500W, frequency 40kHz, and time 30min to obtain a mixed solution;
[0061] S31, heat-treating the mixed solution to cause the covalent organic framework material precursor to undergo a polymerization reaction to generate a covalent organic framework material buffer layer, and making the covalent organic framework material buffer layer adhere to at least a portion of the surface of the silicon nanosheet to obtain a silicon-based negative electrode.
[0062] Specifically, the mixed solution is heat treated at a heating temperature of 130° C. and a heating time of 64 hours to obtain a sandwich silicon-based negative electrode with a covalent organic framework material buffer layer on the surface.
[0063] In addition, the mixed solution after heat treatment was centrifuged and washed with DMF and ethanol in sequence to obtain a silicon-based negative electrode product.
[0064] Example 2
[0065] S12, obtaining a covalent organic framework material precursor;
[0066] Specifically, TAPA and naphthalenetetracarboxylic dianhydride were dissolved in DMF, the molar ratio of TAPA to naphthalenetetracarboxylic dianhydride was 3:2, and 200 mL of DMF was added for each mole of naphthalenetetracarboxylic dianhydride dissolved;
[0067] S22, first mixing the covalent organic framework material precursor and the silicon nanosheets to obtain a mixed solution;
[0068] Specifically, 200 nm average size silicon nanosheets are uniformly dispersed in the above covalent organic framework material precursor, the molar ratio of silicon nanosheets to naphthalenetetracarboxylic dianhydride is 20:1, and ultrasonic dispersion is adopted: power 500W, frequency 40kHz, and time 30min to obtain a mixed solution;
[0069] S32, heat-treating the mixed solution to cause the covalent organic framework material precursor to undergo a polymerization reaction to generate a covalent organic framework material buffer layer, and making the covalent organic framework material buffer layer adhere to at least a portion of the surface of the silicon nanosheet to obtain a silicon-based negative electrode.
[0070] Specifically, the mixed solution is heat treated at a heating temperature of 130° C. and a heating time of 64 hours to obtain a sandwich silicon-based negative electrode with a covalent organic framework material buffer layer on the surface.
[0071] In addition, the mixed solution after heat treatment was centrifuged and washed with DMF and ethanol in sequence to obtain a silicon-based negative electrode product.
[0072] Example 3
[0073] S13, obtaining a covalent organic framework material precursor;
[0074] Specifically, TAPA and perylenetetracarboxylic dianhydride were dissolved in DMF, the molar ratio of TAPA to perylenetetracarboxylic dianhydride was 3:2, and 200 mL of DMF was added for each mole of perylenetetracarboxylic dianhydride dissolved;
[0075] S23, first mixing the covalent organic framework material precursor and the silicon nanosheets to obtain a mixed solution;
[0076] Specifically, 200 nm average size silicon nanosheets are uniformly dispersed in the above covalent organic framework material precursor, the molar ratio of silicon nanosheets to perylene tetracarboxylic dianhydride is 20:1, and ultrasonic dispersion is used: power 500W, frequency 40kHz, and time 30min to obtain a mixed solution
[0077] S33, heat-treating the mixed solution to cause the covalent organic framework material precursor to undergo a polymerization reaction to generate a covalent organic framework material buffer layer, and making the covalent organic framework material buffer layer adhere to at least a portion of the surface of the silicon nanosheet to obtain a silicon-based negative electrode.
[0078] Specifically, the mixed solution is heat treated at a heating temperature of 130° C. and a heating time of 64 hours to obtain a sandwich silicon-based negative electrode with a covalent organic framework material buffer layer on the surface.
[0079] In addition, the mixed solution after heat treatment was centrifuged and washed with DMF and ethanol in sequence to obtain a silicon-based negative electrode product.
[0080] Example 4
[0081] S14, obtaining a covalent organic framework material precursor;
[0082] Specifically, TAPA and pyromellitic anhydride were dissolved in DMF, the molar ratio of TAPA to pyromellitic anhydride was 4:2, and 200 mL of DMF was added for each mole of pyromellitic anhydride dissolved;
[0083] S24, first mixing the covalent organic framework material precursor and the silicon nanosheets to obtain a mixed solution;
[0084] Specifically, 200 nm average size silicon nanosheets are uniformly dispersed in the above covalent organic framework material precursor, the molar ratio of silicon nanosheets to pyromellitic anhydride is 20:1, and ultrasonic dispersion is used: power 500W, frequency 40kHz, and time 30min to obtain a mixed solution
[0085] S34, heat-treating the mixed solution to cause the covalent organic framework material precursor to undergo a polymerization reaction to generate a covalent organic framework material buffer layer, and making the covalent organic framework material buffer layer adhere to at least a portion of the surface of the silicon nanosheet to obtain a silicon-based negative electrode.
[0086] Specifically, the mixed solution is heat treated at a heating temperature of 130° C. and a heating time of 64 hours to obtain a sandwich silicon-based negative electrode with a covalent organic framework material buffer layer on the surface.
[0087] In addition, the mixed solution after heat treatment was centrifuged and washed with DMF and ethanol in sequence to obtain a silicon-based negative electrode product.
[0088] Example 5
[0089] S15, obtaining a covalent organic framework material precursor;
[0090] Specifically, TAPA and pyromellitic anhydride were dissolved in DMF, the molar ratio of TAPA to pyromellitic anhydride was 3:2, and 200 mL of DMF was added for each mole of pyromellitic anhydride dissolved;
[0091] S25, first mixing the covalent organic framework material precursor and the silicon nanosheets to obtain a mixed solution;
[0092] Specifically, 200 nm average size silicon nanosheets are uniformly dispersed in the above covalent organic framework material precursor, the molar ratio of silicon nanosheets to pyromellitic anhydride is 20:1, and ultrasonic dispersion is used: power 500W, frequency 40kHz, and time 30min to obtain a mixed solution
[0093] S35, heat-treating the mixed solution to cause the covalent organic framework material precursor to undergo a polymerization reaction to generate a covalent organic framework material buffer layer, and making the covalent organic framework material buffer layer adhere to at least a portion of the surface of the silicon nanosheet to obtain a silicon-based negative electrode.
[0094] Specifically, the mixed solution is heat treated at a heating temperature of 170° C. and a heating time of 72 hours to obtain a sandwich silicon-based negative electrode with a covalent organic framework material buffer layer on the surface.
[0095] In addition, the mixed solution after heat treatment was centrifuged and washed with DMF and ethanol in sequence to obtain a silicon-based negative electrode product.
[0096] Comparative Example 1
[0097] Silicon nanosheets are used as silicon-based negative electrodes.
[0098] The silicon-based negative electrodes obtained in Examples 1 to 5 and Comparative Example 1 were used to prepare button cells, respectively, and half-cell tests were performed on the corresponding button cells. The test results are shown in Table 1.
[0099] Table 1 Half-cell test results
[0100] Serial number Initial gram capacity mAh / g 100-week capacity retention rate % Example 1 2440 61.4% Example 2 2403 69.8% Example 3 2317 71.3% Example 4 2210 75.5% Example 5 2282 74.5% Comparative Example 1 2650 15.6%
[0101] As can be seen from Table 1, the covalent organic framework material has lithium storage properties and will not significantly reduce the battery capacity. The difference between the initial capacity of the button batteries of Examples 1 to 5 and the initial capacity of the button battery of Comparative Example 1 is not very obvious; after 100 cycles of testing, the capacity of the button batteries of Examples 1 to 5 is still maintained at more than 60%, while the capacity of the button battery of Comparative Example 1 is greatly reduced to 15.6%. It can be clearly seen that the strong constraint buffering effect of the covalent organic framework material in the silicon-based negative electrode can fully suppress and buffer the huge volume change caused by the silicon nanosheets during the charging and discharging process, that is, the expansion rate of the silicon-based negative electrode is greatly reduced, thereby keeping the silicon nanosheets from being pulverized and structurally damaged due to the stress generated by excessive expansion during the cycle, thereby improving its cycle stability and significantly improving the cycle life.
[0102] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:
[0103] (1) Covalent organic framework materials have high chemical stability and great elasticity. Their strong constraint buffering effect can fully suppress and buffer the huge volume change caused by silicon nanosheets during the charging and discharging process, reduce the consumption of electrolyte, and form a uniform, stable and strong SEI film, thereby improving the long cycle and rate performance of the battery cell;
[0104] (2) Covalent organic framework materials do not contain any metal elements, and the synthetic raw materials used are common organic raw materials with wide sources, no pollution and low cost;
[0105] (3) Covalent organic framework materials have lithium storage properties and will not significantly reduce battery capacity.
[0106] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a silicon-based negative electrode, characterized in that: The method comprises: Obtaining a covalent organic framework material precursor; The covalent organic framework material precursor is first mixed with silicon nanosheets to obtain a mixed solution; The mixed solution is heat-treated to make the covalent organic framework material precursor undergo a polymerization reaction to generate a covalent organic framework material buffer layer, and the covalent organic framework material buffer layer is attached to at least a portion of the surface of the silicon nanosheet to obtain a silicon-based negative electrode.
2. The method according to claim 1, characterized in that The method for obtaining a covalent organic framework material precursor comprises: The tri(4-aminophenyl)amine, the dibasic anhydride monomer and the solvent are mixed for a second time to obtain a covalent organic framework material precursor.
3. The method according to claim 2, characterized in that The dibasic anhydride monomer includes at least one of the following: pyromellitic dianhydride, naphthalenetetracarboxylic dianhydride, and perylenetetracarboxylic dianhydride.
4. The method according to claim 2, characterized in that: The molar ratio of the tris(4-aminophenyl)amine to the dibasic anhydride monomer is (3:2) to (4:2).
5. The method according to claim 2, characterized in that: The solvent is an amide solvent.
6. The method according to claim 2 or 5, characterized in that: The solvent is 150 mL to 250 mL relative to 1 mol of the dibasic anhydride monomer.
7. The method according to claim 2, characterized in that The molar ratio of the silicon nanosheets to the dibasic anhydride monomer is (20:1) to (40:1).
8. The method according to claim 1 or 2, characterized in that: The process parameters of the heat treatment include: a heating temperature of 120° C. to 180° C. and a heating time of 56 h to 80 h.
9. A silicon-based negative electrode prepared by the method according to any one of claims 1 to 8.
10. A battery, characterized in that: The battery comprises the silicon-based negative electrode according to claim 9.
Citation Information
Patent Citations
Composite flexible electrode material as well as preparation method and application thereof
CN104103812A
SiOx-based composite negative electrode material, pole piece and preparation method
CN117393718A
Covalent organic framework / porous carbon sphere composite material as well as preparation method and application thereof
CN118136812A
Modified negative electrode material and modification method and application thereof
CN118156493A
An organic light-emitting display device
KR1020250021106A